From Melody to Modesty: The Semiotic Interplay of Sherine’s Abdel-Wahab's 'Kalam Eineh' and the Consumption of Abaya Trends on TikTok - Inayah Amaliah Mutmainnah; Fitriani Fitriani; Haeruddin Haeruddin (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This article discusses the semiotic meaning in the song Kalam Eineh by Sherine Abdel Wahab and its relationship to the phenomenon of using abaya on the TikTok platform as part of popular cultural representation. This research is in the realm of cultural and semiotic studies, with the aim of revealing how popular music and traditional fashion play a role in shaping social and ideological meanings in the digital space. This topic was chosen because the abaya trend on TikTok reflects the negotiation between tradition, modernity, and religious identity, which until now has rarely been studied in depth. The method used is descriptive qualitative with Roland Barthes' semiotic analysis which emphasizes three layers of meaning, namely denotation, connotation, and myth. To strengthen the validity of the analysis, this study also uses theoretical triangulation through Appadurai's view of mediascapes, Giddens on agency and structure, and Hall on representation and negotiation of meaning. The results of the study show that at the level of denotation, songs represent romantic expressions, while abaya serves as clothing; at the level of connotation, both feature symbols of lifestyle, identity, and piety. Meanwhile, at the mythical level, the abaya has undergone a transformation into a popular culture icon that naturalizes the ideology of religiosity, modernity, and aesthetics in digital culture. This research contributes to the study of popular culture and media by emphasizing the relevance of Barthes' semiotic theory in reading contemporary cultural texts in the era of social media.